Improving the photoresponse performance of monolayer MoS2 photodetector via local flexoelectric effect. (18th June 2022) - Feng, Pu; Zhao, Sixiang; Dang, Congcong; He, Sixian; Li, Ming; Zhao, Liancheng; Gao, Liming
Abstract: Strain engineering is an effective means of modulating the optical and electrical properties of two-dimensional materials. The flexoelectric effect caused by inhomogeneous strain exists in most dielectric materials, which breaks the limit of the materials' non-centrosymmetric structure for piezoelectric effect. However, there is a lack of understanding of the impact on optoelectronic behaviour of monolayer MoS2 photodetector via local flexoelectric effect triggered by biaxial strain. In this paper, we develop a probe tip (Pt)-MoS2 -Au asymmetric Schottky barrier photodetector based on conductive atomic force microscopy to investigate the impact of flexoelectric effect on the photoresponse performance. Consequently, when the probe force increases from 24 nN to 720 nN, the photocurrent, responsivity and detectivity increase 28.5 times, 29.6 times and 5.3 times at forward bias under 365 nm light illumination, respectively. These results indicate that local flexoelectric effect plays a critical role to improve the photoresponse performance of photodetector. Our approach suggests a new route to improve the performance of photodetectors by introducing local flexoelectric polarization field, offering the potential for the application of strain modulated photoelectric devices.